Clustering of Laser Scanner Perception Points of Maize Plants. (1st June 2017) - Reiser, D.; Vázquez-Arellano, M.; Izard, M. Garrido; Paraforos, D. S.; Sharipov, G.; Griepentrog, H. W.
Abstract : The goal of this work was to cluster maize plants perception points under six different growth stages in noisy 3D point clouds with known positions. The 3D point clouds were assembled with a 2D laser scanner mounted at the front of a mobile robot, fusing the data with the precise robot position, gained by a total station and an Inertial Measurement Unit. For clustering the single plants in the resulting point cloud, a graph-cut based algorithm was used. The algorithm results were compared with the corresponding measured values of plant height and stem position. An accuracy for the estimated height of 1.55 cm and the stem position of 2.05 cm was achieved.